Plasma Biochemistries and Morphometric Indices of Body Condition in Imperial Cormorant (Phalacrocorax atriceps) Chicks - Gallo, Luciana (2017)
Plasma biochemistries provide a complementary method for assessing physiological and nutritional status of free-ranging wild birds. Triglycerides, total protein and alkaline phosphatase were determined in 110 free-living Imperial Cormorant (Phalacrocorax atriceps) chicks aged 16-35 days, at Punta León (Argentina) during 2010 and 2011. Body mass at 30 days of age ("pre-fledging body condition", 2010 only) and body mass corrected by tarsus length at the time of blood sampling ("current body condition", 2011 only) were also determined. Variability of parameters by sex, hatching order, survival, age and breeding season was assessed, and the relationship between biochemical and morphometric indices was also explored. Morphometric indices were higher in A-chicks (pre-fledging body condition also varied with sex), and explained 35-55% of B-chick survival. Biochemistries differed significantly between breeding seasons, being higher in 2011. Alkaline phosphatase increased with age, and total protein was higher in A-chicks. Triglycerides and total protein accounted for 26% and 30%, respectively, of variation in current body condition; however, they did not forecast pre-fledging body condition. Lastly, total protein levels predicted B-chick survival (higher levels in surviving B-chicks), but their prognostic value was relatively low. The results suggest that unlike morphometric indices, the biochemistries chosen are valuable to assess individual body condition at the time of sampling, yet their applicability for predicting chick survival requires further evaluation.